Differential Activity of Antioxidant Enzymes and Physiological Changes in Wheat (Triticum aestivum L.) Under Drought Stress - Kamal MIRI-HESAR; Ali DADKHODAIE; Saideh DOROSTKAR; Bahram HEIDARI (Notulae Scientia Biologicae, 2019)
Drought stress is one of the most significant environmental factors restricting plant production all over the world. In arid and semi-arid regions where drought often causes serious problems, wheat is usually grown as a major crop and faces water stress. In order to study drought tolerance of wheat, an experiment with 34 genotypes including 11 local and commercial cultivars, 17 landraces, and six genotypes from International Maize and Wheat Improvement Center (CIMMYT) was conducted at the experimental station, School of Agriculture, Shiraz University, Iran in 2010-2011 growing season. Three different irrigation regimes (100%, 75% and 50% Field Capacity) were applied and physiological and biochemical traits were measured for which a significant difference was observed in genotypes. Under severe water stress, proline content and enzymes’ activities increased while the relative water content (RWC) and chlorophyll index decreased significantly in all genotypes. Of these indices, superoxide dismutase (SOD) and RWC were able to distinguish tolerant genotypes from sensitives. Moreover, yield index (YI) was useful in detecting tolerant genotypes. The drought susceptibility index (DSI) varied from 0.40 to 1.71 in genotypes. These results indicated that drought-tolerant genotypes could be selected based on high YI, RWC and SOD and low DSI. On the whole, the genotypes 31 (30ESWYT200), 29 (30ESWYT173) and 25 (Akbari) were identified to be tolerant and could be further used in downstream breeding programs for the improvement of wheat tolerance under water limited conditions.